Exploring Mathematical Critical Thinking Skills of Yogyakarta Junior Secondary School Students - Elsa Susanti; Endah Retnowati (SEAMEO Regional Centre for QITEP in Mathematics, 2018)
This article explores the skills and difficulties in critical thinking of junior Indonesian high school students in mathematics learning. Fifty students of grade IX who were purposive randomly selected from state junior secondary schools in Yogyakarta City were involved as the research subjects. The data were obtained from the test of mathematical critical thinking on the material of geometry. The test consisted of four items that describe each aspect of critical thinking skills, namely interpretation, analysis, evaluation, and inference. The analysis was done by showing the steps of the students ‘answers. The result indicated that the average of the aspects of mathematical critical thinking of students were on the high criteria with students’ greatest difficulties being in the analysis standard. Meanwhile,the average student success in the interpretation standard was 82%, the standard of the analysis was 46.25%, the evaluation standard was 78.25%, and the inference standard was 77%. Furthermore, from the results of the sample students’ exploration answers, it is expected that future teaching should not only focus on fluency in calculation but also on training the students in how to explain the solution steps of the problem solving process as this is important part in critical thinking.